Merkel Cells in Somatosensation - Haeberle, Henry (2008)
Merkel cells are rare epidermal cells whose function in the skin is still debated. These cells localize to highly touch-sensitive areas of vertebrate epithelia, including palatine ridges, touch domes and finger tips. In most cases, Merkel cells complex with somatosensory afferents to form slowly adapting touch receptors; it is unclear, however, whether mechanosensory transduction occurs in the Merkel cell, the somatosensory afferent or both. Classic anatomical results suggests that Merkel cells are sensory cells that transduce mechanical stimuli and then communicate with sensory afferents via neurotransmission. This model is supported by recent molecular, immunohistochemical and physiological studies of Merkel cells in vitro and in intact tissues. For example, Merkel cells express essential components of presynaptic machinery, including molecules required for release of the excitatory neurotransmitter glutamate. Moreover, Merkel cells in vitro and in vivo are activated by mechanical stimuli, including hypotonic-induced cell swelling. Although these findings support the hypothesis that Merkel cells are sensory receptor cells, a definitive demonstration that Merkel cells are necessary and sufficient to transduce touch awaits future studies.